On wireless energy harvesting based relaying for interference-limited user : a DMT perspective - Rao, Yepuri Sudhakara (2020)
In this paper, the diversity-multiplexing tradeoff (DMT) is investigated for an interference-limited relay-aided communication system in the moderate interference regime. Further, in the proposed system, the relay node is powered by wireless energy harvesting (WEH). In particular, this work studies the impact of energy harvest duration at the relay node on the achievable DMT of an interference-limited user using a variant of dynamic decode-and-forward based protocol. Our results show that the DMT of interference-limited user degrades with the proportional increase in energy harvest duration at low multiplexing gains. On the other hand, it is observed that the DMT of WEH-based interference-limited user approaches that of non-EH-based counterpart for higher multiplexing gains.